2011
DOI: 10.3346/jkms.2011.26.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Parenchymal Tuberculosis Sequelae on Mediastinal Lymph Node Staging in Patients with Lung Cancer

Abstract: Because tuberculous (TB) involvement of mediastinal lymph nodes (LN) could cause false positive results in nodal staging of lung cancer, we examined the accuracy of nodal staging in lung cancer patients with radiographic sequelae of healed TB. A total of 54 lung cancer patients with radiographic TB sequelae in the lung parenchyma ipsilateral to the resected lung, who had undergone at least ipsilateral 4- and 7-lymph node dissection after both chest computed tomography (CT) and fluorodeoxyglucose (FDG)-positron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…1). The characteristics of the 56 studies was shown in Supporting Information Table 1 4–6, 14, 23–74. Among the included studies, 46 evaluated LN metastatic disease and 13 assessed extrathoracic metastatic disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The characteristics of the 56 studies was shown in Supporting Information Table 1 4–6, 14, 23–74. Among the included studies, 46 evaluated LN metastatic disease and 13 assessed extrathoracic metastatic disease.…”
Section: Resultsmentioning
confidence: 99%
“…0.91, p = 0.33), suggesting that NSCLC patients with tuberculosis might be more difficult to confirm. The low specificity was not unexpected as tuberculosis can cause lymph node enlargement and hypermetabolism and thus increases the false‐positive rate 30. Besides, three studies included a large number of patients with surgically resectable NSCLC, and thus more early‐stage patients with microscopic metastatic nodes were included, which might be the reason of the low sensitivity 30–32…”
Section: Discussionmentioning
confidence: 99%
“…The detection of extrapulmonary lesions is particularly useful, as obtaining tissue or fluid for analysis may not always be possible or may be invasive. Many studies have been conducted to distinguish avid TB from malignancy and other granulomatous conditions [ 68 71 ]. Since 18 F-FDG is a nonspecific tracer, it cannot reliably distinguish tuberculomas from malignant lung lesions and frequently gives rise to a false-positive diagnosis in patients evaluated for malignancy [ 72 74 ].…”
Section: Diagnosis Of Tuberculosismentioning
confidence: 99%
“…However, it is clear that meticulous risk assessment of the tuberculosis incidence in patients suffering from lung cancer should be carried out [10,11].…”
Section: Discussionmentioning
confidence: 99%